Parallel Planes - Wegner, Nicole (Germany, 2017)
The documentary portrays 12 American avant-garde & punk-rock musicians. It is a journey between genres, an essay on free thinking and an intimate look at how 12 critical players relate to the potential of music.
Verzio Film Festival Submission
Keywords: Documentary films